Evaluation of Ethanol Grade on the Robustness of Acid Number Determination in Fish Oil - Purbaningtias, Tri Esti; Sandy (Indonesian Journal of Chemical Analysis (IJCA), 2024)
The robustness evaluation of the acid number analysis method in fish oil was carried out to see the effect of the type of ethanol used as a solvent in the titration process. The types of ethanol used in this study were pro analysis grade, pharma and food grade, and technical grade. The acid number values (mgKOH/g) in fish oil with various solvents obtained were 2.3955±0.3211 for pro analysis grade; 2.7932±0.2983 for pharma and food grade; 2.7812±0.3362 for technical grade 1; 2.7031±0.3405 for technical grade 2. The acid number for all types of ethanol has a value that is in accordance with the requirements of SNI 8467: 2018 where the acid number value must be less than 3 mgKOH/g. However, if the measurement uncertainty value is included in the calculation, only the pro analysis grade ethanol solvent has an acid number value that is in accordance with the requirements of SNI. The results of the ANOVA test also showed that there was a significant difference in the variation of ethanol types for determining acid numbers because the calculated F value (13.9004) was greater than the F table (3.0984). Therefore, the solvent that must be used in the method of determining acid numbers in fish oil is pro analysis grade ethanol.